THE MULTIPLE APPROACHES OF GROUNDED THEORY: JUSTIFICATION FOR STRAUSSIAN VERSION - Muhaiyuddin, Nor Syafini Mohd; Bakar, Hanif Suhairi Abu; Hussin, Huzili (PEOPLE: International Journal of Social Sciences, 2016)
Qualitative researchers incline to develop a theory or seek for a form of meaning on the basis of data collection. They also do not build their research on pre-arranged hypotheses. Nevertheless, they obviously recognize a problem or subject they aim to examine. Qualitative research gives a flexible approach to researchers and using multiple sources to confirm results. This paper focuses on primary books review of chronological grounded theory as one of qualitative research methods in different versions, then the preference for Straussian version of grounded theory.